Decentralized system for construction projects data management using blockchain and IPFS - Adel, Kareem; Elhakeem, Ahmed; Marzouk, Mohamed (Journal of Civil Engineering and Management, 2023)
Construction projects’ performance is not self-regulating. Therefore, a continuous progress tracking and monitoring process is highly demanded to avoid potential deviations or misalignments. The current practice for the progress tracking and monitoring process suffers from heavily intermediated workflows, human errors, transfer latencies, inaccuracies, and/or information holes. Such issues could gradually lead to severe delays or even complete project failure. This research introduces a novel Peer-to-Peer (P2P) system that relies on Blockchain Technology (BT) and Inter-Planetary File System (IPFS) for managing progress information and as-built digital assets or files. The system is developed based on a three-step approach. First, two chaincodes are formulated for mapping and governing the data operations. Second, a private blockchain network is configured based on Hyperledger Fabric as a hosting platform, including the relevant stakeholders. Third, a private IPFS network is configured and coupled with a cluster service to manage and distribute the off-chain visuals and as-built digital assets. A case study for a non-residential construction project is utilized to test and verify the system’s practicability and assess its performance. The research significance is anticipated in diverse practical areas, including but not limited to; boosting coordination and trust among stakeholders, tracing progressive elaboration of As-built digital assets, accelerating incremental payments processing, assessing overall project performance and on-site productivity, supporting delay analysis and claim/dispute management, and streamlining data flow between the construction phase and the operation and maintenance phase. Further, the system’s future is mapped by evolving it as a sub-unit in a more advanced data model.